Matrimonio y procreación en la ortodoxia eugénica argentina - Miranda, Marisa Adriana (Centro de Investigaciones Socio Históricas. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2005)
In this paper the influence of eugenics - discipline systematized by Francis Galton towards ends of XIX century- in Argentine legal history, making particular emphasis in the regulation of the married institution and the diverse public politics that regulated the human reproduction. In this context, the impression of Galton underlying to the normative incarnation of the legislation on married impediments and to the diverse incentives to increase population of selective type orchestrated in Argentina, not only allows us to visualize the orthodox eugenic thesis, but that also it notices to us on the long-lasting of these concepts until the last decades of XX century.